Cyathea gigantea (Cyatheaceae) as an antimicrobial agent against multidrug resistant organisms - Kathakali Nath; Anupam Das Talukdar; Mrinal Kanti Bhattacharya; Deepshikha Bhowmik; Shiela Chetri; Debarati Choudhury; Abhijit Mitra; Nargis Alom Choudhury (BMC, 2019)
Abstract Background Rapid emergence of multidrug resistant (MDR) organisms in hospital and community settings often result into treatment failure, thus leading the clinicians with fewer treatment options. Cyathea gigantea, an ethnomedicinally important fern used in cuts and wound infections. So, if this medicinal plant is used in treating the MDR infections then it might bring certain relief in future treatment options. Methods Antibacterial activity of C. gigantea against MDR bacteria was assed using well diffusion and broth microdilution methods to determine the diameters of growth inhibition zones, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Synergistic activity was also determined with the conventional antibiotics by disc diffusion method followed by FIC index of each of the tested antibiotic was calculated. The active extract was then subjected to fractionation by column chromatography and antibacterial activity was done with each of the collected fractions. Results Crude extract of C. gigantea was found to be active against all the tested organisms. The MIC was 200 μg/ml against Gram-positive i.e., Staphylococcus aureus ATCC 25923 and 400 μg/ml against Gram-negative i.e., Escherichia coli ATCC 25922 and Pseudomonas aeruginosa PAO1, while the MBC was 400 μg/ml in case of Gram-positive and 800 μg/ml for Gram-negative. The synergistic activity revealed that the plant extract increased the antibacterial property of the studied antibiotics and the FIC index showed that significant synergistic activity was shown by ciprofloxacin followed by tetracycline, ampicillin and oxacillin. Antibacterial activity with the fractionated extract showed that the FR II, FR III and FR IV were active against both Gram-positive and Gram-negative bacteria, whereas FR I, FR V and FR VI did not show antibacterial property against any of the tested bacteria. Conclusions Extracts of C. gigantea was found active against both selected Gram-positive and Gram-negative organisms and thus offers the scientific basis for the traditional use of the fern. The present study also provides the basis for future study to validate the possible use against multidrug resistant organisms.